Fables as a Strategic Space for Instilling Moral Values: A Study of Character Education in the Anthology of Folktales from the Special Region of Yogyakarta - Saudah, Khalifatun; Saleh, Muhammad; Hajrah, Hajrah (Universitas Muhammadiyah Mataram, 2026)
This study investigates fables as a strategic medium for cultivating moral values in character education, using eight fables from Antologi Cerita Rakyat Daerah Istimewa Yogyakarta by Dhanu Priyo Prabowo as the primary source. It aims to analyze how moral values are embedded in the narratives and to examine their relevance through Thomas Lickona’s framework of moral knowing, moral feeling, and moral action, as well as to identify recurring character patterns and their implications for contemporary character education. A qualitative descriptive method was employed. Data were collected through close reading and note-taking, followed by categorization of moral conflicts and identification of narrative elements reflecting moral values. The analysis was guided by Lickona’s framework, with validity ensured through theoretical triangulation. The findings show that the fables convey moral values such as honesty, humility, loyalty, perseverance, prudence, empathy, and wisdom through character behavior and narrative consequences. These values form consistent patterns of character development integrating cognitive, affective, and behavioral dimensions. The fables also reflect Javanese local wisdom, supporting culturally responsive character education. In conclusion, fables function as both cultural heritage and effective pedagogical tools for fostering moral awareness and strengthening learners’ cultural identity.